Recommendation for a definition of acute symptomatic seizure - Beghi, Ettore; Carpio, Arturo; Forsgren, Lars; Hesdorffer, Dale C.; Malmgren, Kristina; Sander, Josemir W.; Tomson, Torbjorn; Hauser, W. Allen (Epilepsia (Copenhagen), 2010)
Summary Purpose:  To consider the definition of acute symptomatic seizures for epidemiological studies, and to refine the criteria used to distinguish these seizures from unprovoked seizures for specific etiologies. Methods:  Systematic review of the literature and of epidemiologic studies. Results:  An acute symptomatic seizure is defined as a clinical seizure occurring at the time of a systemic insult or in close temporal association with a documented brain insult. Suggestions are made to define acute symptomatic seizures as those events occurring within 1 week of stroke, traumatic brain injury, anoxic encephalopathy, or intracranial surgery; at first identification of subdural hematoma; at the presence of an active central nervous system (CNS) infection; or during an active phase of multiple sclerosis or other autoimmune diseases. In addition, a diagnosis of acute symptomatic seizure should be made in the presence of severe metabolic derangements (documented within 24 h by specific biochemical or hematologic abnormalities), drug or alcohol intoxication and withdrawal, or exposure to well‐defined epileptogenic drugs. Discussion:  Acute symptomatic seizures must be distinguished from unprovoked seizures and separately categorized for epidemiologic purposes. These recommendations are based upon the best available data at the time of this report. Systematic studies should be undertaken to better define the associations in question, with special reference to metabolic and toxic insults, for which the time window for the occurrence of an acute symptomatic seizure and the absolute values for toxic and metabolic dysfunction still require a clear identification.